1964
DOI: 10.1002/jsfa.2740150303
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the chemical composition of apples during development, and near picking time

Abstract: During the development of apples the most striking difference in mineral uptake is that between the potassium and calcium patterns. Potassium uptake continues throughout growth, being an essential constituent of the buffer system in the vacuole. Calcium uptake falls off appreciably after the initial period of cell division. It is suggested that the initial supply or availability of calcium in the tree may be of importance in determining the later development of physiological disorders. The mineral content of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0
1

Year Published

1964
1964
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 15 publications
2
6
0
1
Order By: Relevance
“…This lowering of starch content is consistent with previous data for apples22, 24 and bananas 5. Actually, the starch is often used to detect optimal harvest maturity,27 which was done also in this study.…”
Section: Resultssupporting
confidence: 92%
“…This lowering of starch content is consistent with previous data for apples22, 24 and bananas 5. Actually, the starch is often used to detect optimal harvest maturity,27 which was done also in this study.…”
Section: Resultssupporting
confidence: 92%
“…Calcium is the only element where the relationship between tbe end of cell division and reduced movement into fruit has previously been discussed (Wilkinson & Perring, 1964;Wilkinson, 1968;Ferguson, 1980). There is little information concerning similar patterns of accumulation for elements like manganese and zinc since few longitudinal studies examining the elemental distribution and content in fruit over time bave been published (see reviews by Bollard, 1970 andMarschner, 1983).…”
Section: Table 4 Concentration Of Mineral Nutrients In Xylem Sap Fromentioning
confidence: 99%
“…The same principle was used by Beer et al 4 It has been shown, however, that when p-hydroxybenzyl isothiocyanate is treated with alkali it is rapidly and quantitatively split to p-hydroxybenzylalcohol and thiocyanate ion. [6][7] Scharrer et a1. 8 and Ettlinger & Thompson9 determined the thiocyanate ion released from p-hydroxybenzyl isothiocyanate by treatment with alkali.…”
Section: Introductionmentioning
confidence: 99%